PENGARUH TERAPI BERMAIN FLASHCARD UNTUK MENINGKATKAN INTERAKSI SOSIAL ANAK AUTISME DI PUSAT PELAYANAN AUTIS - Pratiwi, Margareta (Universitasdiwangsa Jambi, 2021)
The purpose of this study was to determine the effect of flashcard play therapy to increase socialinteraction of children with autism at the Autism Service Center. Characteristics of researchsubjects include children with autism aged 2-5 years. The number of subjects in this study were 6children, with additional therapist/teacher informants. The results showed that the eye contactcompliance dimension before flashcard therapy had an overall average of 0.333, the averageincreased to 0.75. The Z value is -2.032 with a significant support of 0.042, these results indicatea significant. In the imitation dimension, the overall average value of 0.315 increased to 0.667.The Z value is -1.363 with the support of a significance of 0.173, these results show nosignificance. The receptive language dimension had an overall mean score of 0.288, increasing to0.689. Z is -2.201 with a significance support of 0.028, these results indicate a significant. Theexpressive language dimension has an overall mean score of 0.250, increasing to 0.583. The Zvalue is -1.841 with a significance support of 0.066, this result shows that it is not significant.From the results of the study, it can be concluded that playing flashcard therapy has an effect onimproving eye contact and receptive language skills but has little effect on imitation andexpressive language skills.